Palestine in International Law Perspective - M. Syuib (Law Department, Sharia and Law Faculty., 2016)
The purpose of this research is to determine whether the state of Palestine has met the criteria as a sovereign state or not according to international law perspective. To answer this question, it will be used two theories related to the establishment of statehood, namely; constitutive theory and declarative theory. The constitutive theory stresses that a nation or government may become the subject of the international law if other nations acknowledge them as a state. While the declarative theory emphasizes that a nation can only be classified as statehood if it fulfills the normative criteria as stipulated in the Montevideo Convention, these are; permanent population, a defined territory and government. After analyzed, it is found that Palestine has actually fulfilled the criteria or requirement as a sovereign state based on the two above theories. The state already has permanent population, a defined territory and effective government. Similarly, Palestine has been recognized by 136 countries out of 193 countries in the world. There is only political matter which makes superpower states such as the United States of America have not given yet the recognition to the Palestine. Due to superpower states, more less it will affect Palestine to gain more recognition from other countries. However, Palestine is a sovereign state now based on the international law perspective. The methodology used in this research is by collecting primary resources such as journals, books, the United Nations document and other several secondary resources, and then these are analyzed and come up with a conclusion. Key words: Palestine, Sovereignity, Perspective, International Law.